Effects of liming on nutrient uptake, biomass production and nodulation in Pueraria phaseoloides - Philip A; Antony A P; Joseph M A; Punnoose K I (Indian Journal of Natural Rubber Research, 1995)
Potculture experiments were conducted to study the effects of limiting on the growth of Pueraria phaseoloides and on the changes in soil chemical properties. Liming significantly increased the dry matter production and nodulation of P. phaseoloides. The availability of P, K, Ca and Mg in soil increased significantly by lime application. Liming showed a positive effect on the uptake of N, P, Ca and Mg but had negative effect on the uptake of K.
Keywords: Cover crop; Dry matter production; Lime requirement; Nodulation